New Insights Into Biomphalysin Gene Family Diversification in the Vector Snail Biomphalaria glabrata - Pinaud, Silvain; Tetreau, Guillaume; Poteaux, Pierre; Galinier, Richard; Chaparro, Cristian; Lassalle, Damien; Portet, Anaïs; Simphor, Elodie; Gourbal, Benjamin; Duval, David (Frontiers in Immunology, 2021)
Aerolysins initially characterized as virulence factors in bacteria are increasingly found in massive genome and transcriptome sequencing data from metazoans. Horizontal gene transfer has been demonstrated as the main way of aerolysin-related toxins acquisition in metazoans. However, only few studies have focused on their potential biological functions in such organisms. Herein, we present an extensive characterization of a multigene family encoding aerolysins - named biomphalysin - in Biomphalaria glabrata snail, the intermediate host of the trematode Schistosoma mansoni. Our results highlight that duplication and domestication of an acquired bacterial toxin gene in the snail genome results in the acquisition of a novel and diversified toxin family. Twenty-three biomphalysin genes were identified. All are expressed and exhibited a tissue-specific expression pattern. An in silico structural analysis was performed to highlight the central role played by two distinct domains i) a large lobe involved in the lytic function of these snail toxins which constrained their evolution and ii) a small lobe which is structurally variable between biomphalysin toxins and that matched to various functional domains involved in moiety recognition of targets cells. A functional approach suggests that the repertoire of biomphalysins that bind to pathogens, depends on the type of pathogen encountered. These results underline a neo-and sub-functionalization of the biomphalysin toxins, which have the potential to increase the range of effectors in the snail’s immune arsenal.